Leadership Style Impact on Employee Performance at Hidayatullah Medan - Fadhlullah, Mhd Zuhri; Ruswanda, Iwan; Fahrozi, Ridwan (Pascasarjana Universitas Pasundan, 2023)
This study analyzes the influence of leadership style on employee performance in implementing organizational policies at the Hidayatullah Medan Main Campus with a descriptive quantitative approach using SPSS version 27. The results of a simple linear regression analysis show that leadership style has a significant effect on employee performance, with t count (2.122) > t table (1.663) and a significant value of 0.037 < 0.05. Employee performance is in the good category with an average percentage of 59.52%, in terms of work quality, work quantity, time effectiveness, punctuality, and independence. Correlation analysis shows an R Square of 0.540, which means that leadership style affects employee performance by 54%, while 46% is influenced by other factors such as work experience, work culture, skills, and work ethic.